The political economy of special needs transfers: Evidence from Bavarian municipalities, 1993-2011 - Thushyanthan Baskaran (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2014)
This paper studies whether higher level governments treat politically aligned municipalities differently than unaligned ones when they provide special discretionary transfers to resolve acute fiscal problems (special needs transfers). By implementing a regression discontinuity design with a sample of municipalities in the German federal state of Bavaria over the period 1993-2011, I show that among the group of municipalities that receive special needs transfers of more than 10,000 Euros, those that are barely aligned with the state government have discontinuously higher debt, higher revenues from user fees and contributions, and higher local tax rates. Before the state government grants special needs transfers to aligned municipalities, they must evidently raise more own source revenues and experience worse fiscal difficulties than unaligned municipalities. Hence, aligned municipalities are treated less leniently.
Keywords: H30; H71; H77; 330; special needs transfers; political alignment; state and local governments